АҲОЛИ ҲУҚУҚИЙ МАДАНИЯТИНИ ЮКСАЛТИРИШ ФУҚАРОЛИК ЖАМИЯТИ ҚУРИШ ГАРОВИ (Scientific journal of the Fergana State University, 2023)
The article points out that the guarantee of establishing a civil society depends on improving the legal culture of the population.